Profit Tax: Problems and Solutions - Khusan Bakhodirovich Zaripov (American Journal of Economics and Business Management, 2023)
In this article, the nature, characteristics and current problems of the mechanism of taxable profit administration based on the current tax legislation were highlighted. At the same time, the article examines the features of the profit tax elements in the practice of taxation, the results of the implementation of fiscal and regulatory tasks of the activities of the taxable profit administration. The economic content of the concept of profit, its formation, economic concepts such as accounting profit and net profit are expressed based on the views of economists. The specific aspects that arise in the process of tax base formation during the process of collecting the profit tax are described. It noted that economic benefit in the form of money or in kind, which is taken into account to the extent that it is possible to assess the benefit, is recognized as income.